Settlement of embankments constructed of unsaturated compacted soil - Annandale, George William (My University, 2014)
The purpose of this investigation was to establish a method to determine settlement in compacted unsaturated soil (with special reference to embankments) by using oedometer test results. A review of the behaviour and the principle of effective stress in unsaturated soil is g i v e n . The conclusion is reached that consolidation in unsaturated soil is largely controlled by the dissipation of excess pore-air pressure. Methods are described to determine the soil parameters that are required to estimate pore-air pressures in unsaturated soil from oedometer tests. A computer program is described to estimate pore-air pressures in embankments at the end of construction and at specified time intervals after completion. A case study on the Mita Hills dam in Zambia is reported and calculated settlements of this embankment are compared with observed settlements.
A Dissertation submitted to the Faculty of Engineering, University of the Witwatersrand , Johannesburg in partial fulfilment of the requirements for the degree of Master of Science in Engineering JOHANNESBURG 1979